Implementation of Continuing Professional Development in Self Professional Development Factors Amongst Aviation Polytechnic’s Lecturers - Pratama, Andrian; Samani, Muchlas; Buditjahjanto, Asto (Pelopor Publikasi Akademika, 2024)
The purpose of this research is to find out the picture of conditions in quantity and quality of lecturers today and the implementation of continuing professional develompent lecturers in terms of self professional development at makassar aviation polytechnic. This research uses a qualitative approach by collecting data in terms of documents, literature, and interviews. The research subject was a makassar aviation polytechnic lecturer who numbered 16 people supported by interviews with 3 people in managerial positions. The implementation of the factors studied is the implementation factor of continuing professional develompent lecturers in terms of self professional development. The results of this study show that the implementation of Continuing Professional Development in aviation polytechnics is still not optimal in terms of quantity. This can be seen from the number of certified lecturers as many as 7 people or 43% of the number of permanent lecturers. Aviation polytechnics do not yet have lecturers with doctoral criteria. There are variables of self professional development, namely in the implementation of Continuing Professional Development in self reading activities are considered good, self development in research activities is considered not optimal, and in academic quality activities is considered Not optimal. These findings indicate that implementation of Continuing Professional Development has not been optimal.